Texas Phoenix Palm Decline - Nigel A. Harrison; Monica L. Elliott (EDIS)
PP-243, a 5-page illustrated fact sheet by Nigel A. Harrison and Monica L. Elliott, describes this new systemic disease affecting primarily date palms in Florida, the pathogen and hosts, symptoms, diagnostics, and disease management. Includes references. Published by the UF Department of Plant Pathology, November 2007.